Clinical and demographic differences in the willingness to use self-administered at-home COVID-19 testing measures among persons with opioid use disorder. Issue 1 (1st December 2022) - Mistler, Colleen B.; Sullivan, Matthew; Wickersham, Jeffrey A.; Copenhaver, Michael M.; Shrestha, Roman
Abstract: Background: COVID-19 is disproportionately affecting disadvantaged populations, including persons with opioid use disorder (OUD). Persons with OUD are at greater risk for direct (e.g., COVID-19 diagnosis, severe symptoms) and indirect consequences (relapse, overdose) of COVID-19. Given stay at home orders, at-home testing options may serve as a viable tool to curb the increase in COVID-19 transmission and adverse effects of COVID-19. Methods: From May to September 2020, we surveyed 110 persons in treatment for OUD about their willingness to use various self-administered at-home COVID-19 testing measures. Participants were stratified by age, gender, and racial-ethnic identity to observe differences in willingness to use COVID-19 tests. The three COVID-19 tests included a throat swab sample, a saliva-based sample, and a blood prick test. Results: A high willingness to use at-home COVID-19 tests was observed in patients in treatment for OUD. A greater proportion of females were willing to use a saliva-based test; greater proportions of White participants were willing to use a saliva based COVID-19 test compared to racial-ethnic minorities. Older aged participants (≥45 years old) reported greater rates of willingness to use a self-administered at home blood prick test for COVID-19. Conclusions: At-home testing measures for COVID-19 appear highly acceptable among people with OUD.